2017
DOI: 10.1111/bioe.12323
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Negotiating the Social Value of Research in Public Health Facilities: Perceptions of Stakeholders in a Research‐Active Province of South Africa

Abstract: This paper reports on qualitative research conducted in KwaZulu-Natal, South Africa, among researchers and gate-keepers of health facilities in the province. Results suggest disparate but not irreconcilable perceptions of the social value of research in provincial health facilities. This study found that researchers tended to emphasise the contribution of research to the generation of knowledge and to the health of future patients while gate-keepers of health facilities tended to emphasise its contribution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…While researchers saw the social value of research in the generated knowledge, regional health managers emphasized the contribution that research makes to the healthcare system and the care of current patients. 24 This finding echoes other literature 25 and raises important and unsolved questions about the value of research within health systems, especially in low-resource settings.…”
Section: Introductionsupporting
confidence: 60%
“…While researchers saw the social value of research in the generated knowledge, regional health managers emphasized the contribution that research makes to the healthcare system and the care of current patients. 24 This finding echoes other literature 25 and raises important and unsolved questions about the value of research within health systems, especially in low-resource settings.…”
Section: Introductionsupporting
confidence: 60%
“…Finally, our study identified social value as the least frequent issue raised by RECs. A recent study found that stakeholders felt social value is an important ethical benchmark that should contribute to scientific knowledge and improve the health care for both current and future patients (Lutge, Slack, & Wassenaar, 2017). Elsewhere, Barsdorf and Millum (2017) argued that the conceptualization of social value should consider both the expected benefits of the research and the priority that the beneficiaries deserve.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Several commentators acknowledge social value as an important ethical benchmark, in that a study should contribute to scientific knowledge generation and improve healthcare for both current and future patients. [12,22,23] There are few empirical studies that have explored stakeholders' views on social value in research. A study in Kenya [24] found that stakeholders considered a study to have social value if it involved benefit-sharing, for example, through post-trial access to medical care, and societal benefits emanating from the successful completion of research.…”
Section: Discussionmentioning
confidence: 99%